2022
DOI: 10.1002/art.42122
|View full text |Cite
|
Sign up to set email alerts
|

Complement C4 Copy Number Variation is Linked to SSA/Ro and SSB/La Autoantibodies in Systemic Inflammatory Autoimmune Diseases

Abstract: Objective Copy number variation of the C4 complement components, C4A and C4B, has been associated with systemic inflammatory autoimmune diseases. This study was undertaken to investigate whether C4 copy number variation is connected to the autoimmune repertoire in systemic lupus erythematosus (SLE), primary Sjögren's syndrome (SS), or myositis. Methods Using targeted DNA sequencing, we determined the copy number and genetic variants of C4 in 2,290 well‐characterized Scandinavian patients with SLE, primary SS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…C4A copy number = 2 HR = 1.89 (CI95%: 0.76-4.68) p = 0.17 HR = 1.15 (CI95%: 0.54-2.45) p = 0.73 difference was seen in the age at first occurrence of nephritis between SLE patients with normal C2 and SLE patients heterozygous for 28-bp C2 deletion who had 2 copies of C4A (P for rs9332736 = 0.73) (Figure 4). In a previous study by our group, we found a strong association between C4A copy number and the presence of autoantibodies against SSA/Ro and SSB/La in systemic inflammatory autoimmune diseases (18), and therefore, we evaluated whether rs9332736 affected the presence of autoantibodies in SLE and primary SS. However, analysis of SSA/Ro, SSB/La, anti-U1 RNP, anti-Sm, and antiphospholipid antibodies in SLE and primary SS patients only showed minor differences when evaluating the role of the 28-bp C2 deletion (Supplementary Figures 3A-E, http:// onlinelibrary.wiley.com/doi/10.1002/art.42270).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C4A copy number = 2 HR = 1.89 (CI95%: 0.76-4.68) p = 0.17 HR = 1.15 (CI95%: 0.54-2.45) p = 0.73 difference was seen in the age at first occurrence of nephritis between SLE patients with normal C2 and SLE patients heterozygous for 28-bp C2 deletion who had 2 copies of C4A (P for rs9332736 = 0.73) (Figure 4). In a previous study by our group, we found a strong association between C4A copy number and the presence of autoantibodies against SSA/Ro and SSB/La in systemic inflammatory autoimmune diseases (18), and therefore, we evaluated whether rs9332736 affected the presence of autoantibodies in SLE and primary SS. However, analysis of SSA/Ro, SSB/La, anti-U1 RNP, anti-Sm, and antiphospholipid antibodies in SLE and primary SS patients only showed minor differences when evaluating the role of the 28-bp C2 deletion (Supplementary Figures 3A-E, http:// onlinelibrary.wiley.com/doi/10.1002/art.42270).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of C4 copy number and HLA alleles from DNA sequencing data. The complement C4 copy numbers for both targeted sequencing data and whole-genome sequencing data were estimated based on read depth using the Germli-neCNVCaller (Genome Analysis Toolkit) as described previously (18), and a brief description can be found in the Supplementary Information. The integer copy number of C4A and C4B was estimated using the relative read depths of 5 single-nucleotide variants in exon 26 specific for C4A and C4B while accounting for the total copy number of C4.…”
Section: Methodsmentioning
confidence: 99%
“…IBM is unique as it has low GCNs in C4T , C4A and C4B . In a study of anti-Ro/anti-La patients with autoimmune diseases including myositis, Lundtoft and colleagues observed low GCNs of C4A in Scandinavian patients 49…”
Section: Discussionmentioning
confidence: 99%
“…In a study of anti-Ro/ anti-La patients with autoimmune diseases including myositis, Lundtoft and colleagues observed low GCNs of C4A in Scandinavian patients. 49 It is worthy pointing out that the effects of GCN variation for C4S and C4B were opposite to those of C4L or C4A in JDM, DM and PM, which suggests different functions of C4S and C4B compared with C4L and C4A. Indeed, short C4 genes associate with higher C4 protein production 50 51 and activated C4B protein generates faster activation of complement pathways 52 ; long C4 genes associate with attenuated C4 protein production but possibly engage in antisense defence against viral infections.…”
Section: Myositismentioning
confidence: 97%
“…They observe a dose‐dependent association between C4A copy number and anti‐SSA/SSB in all 3 diseases. Each decrease in copy number of C4A is associated with an increased risk of the production of both anti‐SSA and anti‐SSB (odds ratio [OR] 5.89 [95% confidence interval (95% CI) 4.83–7.23]), with the presence of either autoantibody (OR 2.37 [95% CI 2.02–2.77]), and with the absence of anti‐SSA and anti‐SSB (OR 1.53 [95% CI 1.36–1.73]) (4). However, the question of whether this is driven by the complement gene remains unproven in this analysis based on these observations alone, due to the extensive LD described above.…”
Section: Figurementioning
confidence: 99%